The book of ceremonies - Constantine VII Porphyrogenitus, Emperor of the East, 905-959.
1 online resource (2 volumes (xxxviii, vi, 870 pages))
Keywords: This is the first modern language translation of the entire text of the tenth-century Greek Book of Ceremonies (De ceremoniis) , a work compiled and edited by the Byzantine emperor Constantine VII (905-959). It preserves material from the fifth century through to the 960s. Chapters deal with diverse subjects of concern to the emperor including the role of the court, secular and ecclesiastical ceremonies, processions within the Palace and through Constantinople to its churches, the imperial tombs, embassies, banquets and dress, the role of the demes, hippodrome festivals with chariot races, imperial appointments, the hierarchy of the Byzantine administration, the equipping of expeditions, including to recover Crete from the Arabs, and the lists of ecclesiastical provinces and bishoprics.